Identification and assessment - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Amsterdam : JAI Press, 2003)
Identification and assessment of learning and behavioural disabilities have long been issues of great concern, and have become increasingly important in recent years. Identification and assessment issues determine how students are characterized as having disabilities, provide implications for treatment, and provide evidence for the success or failure of interventions. In this volume, several topics of relevance to the issue of identification and assessment of learning and behavioural disabilities are discussed by leading scholars, in reviews of recent relevant research, policy analyses, and new investigations with original data. This book is intended for interested professionals and practitioners; researchers in learning and behavioural disabilities; and graduate students in psychology, education, and special education.
Issues in the identification of learning disabilities / Thomas E Scruggs, Margo A Mastropieri -- Starting at the beginning for learning disabilities identification: response to instruction in general education / Deborah L Speece, Dawn Eddy Molloy, Lisa Pericola Case - Identification of non-responders: are the children "left behind" by early literacy intervention the "truly" reading disabled? / Stephanie Al Otaiba -- The role of reading intervention research in the identification of children with reading difficulties: a meta-analysis of the literature funded by the NICHD / Denise M Necoechea, H.Lee Swanson -- Current advances in assessment and intervention for children with learning disabilities / Jack A Naglieri -- Individuals with mental retardation and a sensorimotor disorder: assessment of disability / Giulia Balboni, Patrizia Ceccarani -- Does IQ and reading level influence treatment outcomes? Implications for the definition of learning disabilities / H.Lee Swanson -- Text anxiety, perceived competence, and academic achievement in secondary school students / Daniela Lucangeli, Thomas E Scruggs -- The assessment of self-regulation in college students with and without academic difficulties / Cesare Cornoldi, Rossana DeBeni, Maria Chiara Fioritto.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Learning disabilities -- Diagnosis; Learning disabled children -- Education; Behavioral assessment of children; Teaching of students with specific learning difficulties / needs; Teaching of students with emotional & behavioural difficulties; Education -- Special Education -- Learning Disabilities